A prospective epidemiological study of injuries in four English professional football clubs - Hawkins, R. D.; Fuller, C. W. (British Journal of Sports Medicine, 1999)
OBJECTIVE: To define the causes of injuries to players in English professional football during competition and training. METHOD: Lost time injuries to professional and youth players were prospectively recorded by physiotherapists at four English League clubs over the period 1994 to 1997. Data recorded included information related to the injury, date and place of occurrence, type of activity, and extrinsic Playing factors. RESULTS: In all, 67% of all injuries occurred during competition. The overall injury frequency rate (IFR) was 8.5 injuries/1000 hours, with the IFR during competitions (27.7) being significantly (p < 0.01) higher than that during training (3.5). The IFRs for youth players were found to increase over the second half of the season, whereas they decreased for professional players. There were no significant differences in IFRs for professional and youth players during training. There were significantly (p < 0.01) injuries in competition in the 15 minute periods at the end of each half. Strains (41%), sprains (20%), and contusions (20%) represented the major types of injury. The thigh (23%), the ankle (17%), knee (14%), and lower leg (13%) represented the major locations of injury, with significantly (p < 0.01) more injuries to the dominant body side. Reinjury counted for 22% of all injuries. Only 12% of all injuries were caused by a breach of the rules of football, although player to player contact was involved in 41% of all injuries. CONCLUSIONS: The overall level of injury to professional footballers has been showed to be around 1000 times higher times higher than for industrial occupations generally regarded as high risk. The high level of muscle strains, in particular, indicates possible weakness in fitness training programmes and use of warming up and cooling down procedures by clubs and the need for benchmarking players' levels of fitness and performance. Increasing levels of injury to youth players as a season progresses emphasizes the importance of controlling the exposure of young players to high levels of competition.